A Double-Blind, Randomized, Placebo-Controlled Trial of 17 Alpha-hydroxyprogesterone Caproate in the Management of Preterm Premature Rupture of Membranes - Langen, Elizabeth S.; Sit, Anita; Sherwin, Katie; Lyell, Deirdre J.; Blumenfeld, Yair J.; El-Sayed, Yasser Y. (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate whether weekly administration of 17 α-hydroxyprogesterone caproate (17-OHPC) increases the number of women who achieve 34 weeks of gestation after preterm premature rupture of membranes (PPROM).Study Design We conducted a multicenter double-blind, randomized controlled trial of 17-OHPC versus placebo among women with PPROM. Women with singleton pregnancy, clinically confirmed PPROM, and without evidence of active infection or major fetal malformation between 240/7 and 320/7 weeks of pregnancy were offered enrollment. Women received weekly injections of 17-OHPC versus placebo until 340/7 weeks of gestation or delivery. The remainder of care was per hospital protocol. The primary outcome was achievement of 34 weeks of gestation. Secondary outcomes included length of latency and maternal and fetal outcomes.Results In this study, 21 women were enrolled. Eleven women received placebo and 10 received 17-OHPC. The study was closed prematurely secondary to poor enrollment. None of the women remained pregnant until 34 weeks of gestation. The median latency periods were 8 and 14.5 days for the placebo and 17-OHPC groups, respectively (p = 0.14). There were no differences in maternal or neonatal outcomes.Conclusion We did not identify any benefit from administration of 17-OHPC in pregnancies complicated by PPROM.
Keywords: 17 α-hydroxyprogesterone caproate; latency; preterm birth; preterm premature rupture of membranes